THE EVALUATION OF BLOOD ETHYL ALCOHOL LEVELS OF DRIVERS INVOLVED IN TRAFFIC ACCIDENTS - (:unkn) unknown (NOBEL ILAC, 2016)
Objective: We aimed to evaluate blood alcohol concentrations (BAC) of drivers involved in traffic accidents, to define procedures of blood sampling for BAC analysis and legal sanctions. Material and Method: In 2011 blood samples from 2251 drivers sent to the Chemistry Department of the Council of Forensic Medicine for alcohol determination were analyzed by dual column head-space/gas chromatography flame-ionisation detector (HS/GC-FID). BAC levels above 10 mg/dl were back-extrapolated to the time of crime. Rate of reduction was accepted 15 mg/dl/hr and BAC effects on safe driving skills were discussed. Results: Ethanol was present in 19.4% of drivers. BAC was above 100 mg/dl in more than half of the cases (56.5-64.5%) and was above the allowed level in traffic (50mg/dl) in the majority (78.1-89%). In contravention of legislation, blood sampling was delayed more than two hours following traffic accidents and this created discrepancies in BAC level calculations. Conclusion: Accurate results can be obtained with timely and properly taken blood samples. Health care workers may face serious legal sanctions due to damages that may arise because of blood samples collected contrary to the procedure. An important part of traffic accidents can be prevented with reduction of the allowed BAC in traffic to 30 mg/dl.
Keywords: Traffic accidents; alcohol; blood sampling; driver; LAWS; DRUGS; RISK; AGE